Letter from Arnold O. Beckman to I. H. Lyons - Beckman, Arnold O. (1935)
Though unsigned, context indicates that this letter was written by Beckman. Dr. Arnold O. Beckman (1900-2004) invented the first commercially successful electric pH meter in 1934 and thus began a long career manufacturing scientific and medical instruments with National Technical Laboratories, Arnold O. Beckman, Inc., and Beckman Instruments. After his retirement he devoted his life to philanthropy and specifically supporting scientific innovation. I. H. Lyons provided the impetus for Arnold Beckman's move from academia to business. In 1933, as the president of National Postal Meter Company, Lyons contacted Caltech for help developing an ink that would not clog the postal meters. He began working with Arnold Beckman and the following year formed a subsidiary, National Inking Appliance Co., to manufacture the pungent non-clogging ink. By 1935, the focus moved from ink to pH meters and the name was changed to National Technical Laboratories; Lyons remained involved in the new company. Arnold Beckman invented his first pH meter in 1934 at the request of a chemist from the California citrus industry, who needed an accurate way to measure the acidity of his product. The resulting instrument kicked off rapid development not only of Beckman Instruments, Inc. but also of the electronic scientific instrument industry.
Keywords: Hydrogen-ion concentration--Measurement--Instruments; Scientific apparatus and instruments; Beckman Instruments, Inc.